Load Balancing of node in Network using Ant Colony Optimization - Aher, Vaishnavi; Khairnar, Sayali; Shinde, Madhuri; Shirole, Priyanka (International Journal of Computer Sciences and Engineering, 2015)
In this paper, we used algorithm for load balancing of workload among the various nodes of grid network by using Ant Colony Optimization (ACO). Load balancing is one in all the most difficult problems in networking that is need to distribute the dynamic work across multiple nodes to confirm that no single node is overloaded. The main contribution of our work is to balance the whole system load whereas making an attempt to maximize and minimize the parameter. Actually when two or more co-positioned ants exchange their knowledge, they extend their movement radius to a bigger domain and this causes better awareness of the environment. There is a similar idea which is inspired from the pheromone deposits from the ants while wandering. Other ants can pursue the ant by using this pheromone deposited. This idea is applied in most of ant colony optimization problems.